Radiographic Measurements of the Hip Joint in Capuchin Monkeys (Sapajus spp.) - de Souza Siragusi, Rafael H. [UNESP] (2024)
Background: Radiographs are useful for the initial evaluation of the hip joints. The information can be utilized for the betterment of animal health or other goals such as anatomic studies and gait analysis, among others. Therefore, this study aimed to evaluate radiographic measurements of the hip joint in capuchin monkeys, kept under human care at a reference center for wildlife. Methods: Twelve capuchin monkeys (Sapajus spp.) (three adult males, seven adult females, and two sub-adult females) were evaluated. Ventrodorsal radiographic views were taken under chemical restraint. All measurements on the digital images were performed in triplicate by one examiner. Results and Conclusions: None of the measurements evaluated were statistically different between males and females. No statistical differences were found between hind limbs. The mean (±SD) Norberg angle was 104.92° (±2.82°) and the Wiberg angle was 15.26° (±1.86°). The percentage of the femoral head covered by the acetabulum was 68.57% (±3.65%) and the acetabular index depth to width ratio was 54.66% (±3.85%). In conclusion, the radiographic measurements showed certain morphological features of the hip joint in Sapajus spp. that contribute to improving species knowledge.